The Complexity Register: A Collaborative Tool for System Complexity Evaluation. Issue 1 (2nd January 2022) - Potts, Matthew; Harvey, David; Johnson, Angus; Bullock, Seth
Abstract: As modern engineered systems become ever more connected and interdependent there is an increasing need to evaluate their complexity . However, evaluating system complexity is challenging due to the complicated conceptual landscape of competing definitions of the term complexity itself, and the range of perspectives that can be taken on what constitutes the System of Interest. This paper attempts to overcome these hurdles through introducing a Complexity Register with which to build and record a shared understanding of system complexity for key stakeholders. In order to overcome current challenges in evaluating the complexity of an engineering system, the Complexity Register encourages personnel to adopt a broad range of perspectives on the potential issues, impacts, and mitigations to manage system complexity. The formulation of the Complexity Register is informed by design principles derived from a case study analysis of a system complexity evaluation tool. The Complexity Register should enable more effective shared understanding by encouraging collaboration that makes explicit the multiple viewpoints taken when evaluating system complexity and promoting continued reevaluation throughout a system or project lifecycle.